Thrombosis And Thromboprophylaxis In COVID-19 Patients During Hospitalization And Early Post-discharge Period - Seyed Pouriya, Hosseini Mehr; Valentyn, Smorzhevskyi; Yuliia, Dzekunova; Igor, Dmytrenko (Asian Journal of Medical Sciences, 2021)
While SARS-CoV-2 infection continues to circulate around the world, there are still many uncertainties on how to treat the patients with this potentially deadly virus, and more importantly, for how long! COVID-19 causes many different symptoms, among which coagulopathy seems to play an essential role in the survival prognosis of patients. While medical centers worldwide have developed various algorithms for preventing thrombosis in COVID-19 patients, there are still no clear guidelines on the length of thromboprophylaxis therapy, target groups who should receive suitable anticoagulant prophylaxis, and even the choice of the most appropriate agent for such treatment.